MOOSE HABITAT IN MASSACHUSETTS: ASSESSING USE AT THE SOUTHERN EDGE OF THE RANGE - Wattles, David W.; DeStefano, Stephen (Lakehead University, 2013)
Moose (Alces alces) have recently re-occupied a portion of their range in the temperate deciduous forest of the northeastern United States after a more than 200 year absence. In southern New England, moose are exposed to a variety of forest types, increasing development, and higher ambient temperatures as compared to other parts of their geographic range. Additionally, large-scale disturbances that shape forest structure and expansive naturally occurring shrub-willow communities used commonly elsewhere are lacking. We used utilization distributions to determine third order habitat selection (selection within the home range) of GPS-collared moose. In central Massachusetts, forests regenerating from logging were the most heavily used cover type in all seasons (48 - 63% of core area use). Habitat use of moose in western Massachusetts varied more seasonally, with regenerating forests used most heavily in summer and fall (57 and 46%, respectively), conifer and mixed forests in winter (47 - 65%), and deciduous forests in spring (41%). This difference in habitat selection reflected the transition from northern forest types to more southern forest types across the state. The intensive use of patches of regenerating forest emphasizes the importance of sustainable forest harvesting to moose. This study provides the first assessment of habitat requirements in this southern portion of moose range and provides insights into re-establishment of moose in unoccupied portions of its historic range in New York and Pennsylvania.